Efektivitas Kebijakan Hukum Terkait Hak Asasi Manusia Di Indonesia Dalam Menanggulangi Diskriminasi Rasial - Irwan matias gurlan sinaga; Fadhiil ahmadi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Racial discrimination in Indonesia remains a profound social issue, despite the existence of legal policies designed to address it. This study aims to analyze the effectiveness of legal policies in combating racial discrimination based on existing regulations. Using a juridical-normative method, the research examines various legal literatures, laws, and international conventions, including Law No. 40 of 2008 and the International Convention on the Elimination of All Forms of Racial Discrimination (CERD). The method employed is a library study, involving the collection and analysis of various legal documents and related legal theories. The findings indicate that while legal policies have been implemented, their effectiveness remains limited, primarily due to weak law enforcement and the lack of public awareness regarding their rights. Some existing policies have not been fully effective in reducing racial discrimination, highlighting the need for improvements in the legal system and enhanced legal education for the public. Thus, further efforts are required to achieve more inclusive social justice